Complete genome sequence of the filamentous fungus Aspergillus westerdijkiae reveals the putative biosynthetic gene cluster of ochratoxin A - Chakrabortti, Alolika (2019)
Ochratoxin A (OTA) is a common mycotoxin that contaminates food and agricultural products. Sequencing of the complete genome of Aspergillus westerdijkiae, a major producer of OTA, reveals more than 50 biosynthetic gene clusters, including a putative OTA biosynthetic gene cluster that encodes a dozen of enzymes, transporters, and regulatory proteins.